"Fighting the Good Fight": Why Do Public Defenders Remain on the Job?. (July 2020) - Baćak, Valerio; Lageson, Sarah E.; Powell, Kathleen
In this article, we ask why public defenders remain on the job despite a number of unique and testing work-related challenges. To answer this question, we analyze original data collected through 87 semistructured interviews with public defenders from government, nonprofit, and appointed counsel systems across the United States. Participants explicated a set of intrinsic and extrinsic motivations salient to their decision to remain in public defense: interacting with clients, defending the Constitution, fighting social inequality, pursuing personal values, appreciating camaraderie with colleagues, and earning public sector benefits. We discuss how our findings relate to prior research, identify directions for future studies, and tentatively engage policy implications.